Um possível olhar psicanalítico frente ao pânico - Signori, Caroline (Universidade do Vale do Rio dos Sinos, 2018)
Panic disorder is considered a psychiatric term and has been introduced as a category in 1980. However, this contemporary phenomenon was already been studied and clinically discussed long before this nomenclature by psychoanalysis, which approach this affective state always linked to fear, extreme forms of anguish and phobia. Therefore, the objective of this study is based on broaden the horizons, looking back beyond the psychiatric vision of categorization and description of symptoms of the said disorder. Thus, first, inquiries and reflections will be carried out for the differences between the areas of psychiatry and psychoanalysis. In the second topic, it is proposed the theoretical foundation on the origins and possible causes of the emergence of panic through psychoanalytic concepts related to aspects of the maternal primordial bond. In addition to the bibliographic study, the present work can be used in the analysis of case reports that contribute to a better comprehension of the theme. Was certified the significant contributions of psychoanalysis to the understanding and treatment of this phenomenon so present in the daily life of the human being.
Keywords: Pânico; Psicanálise; Vínculo materno; Panic; Psychoanalysis; Maternal bond